1975
DOI: 10.1002/pssb.2220680214
|View full text |Cite
|
Sign up to set email alerts
|

Interlayer interaction and optical properties of layer semiconductors: 2H and 4H polytypes of PbI2

Abstract: The consequences of layer compound polytypism on optical properties and electronic Die Auswirkungen der Schichtstruktur-Polytypie anf optische Eigenschaften und elek-band structure are investigated for the case of 2H and 4H PbI,.tronische Bandstruktur werden am Beispiel des 2Hund 4H-PbI, untersucht.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

1976
1976
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Absorption peaks at 2.5 eV are also observed in our measurement, which can be attributed to another direct transition in CH 3 NH 3 PbI 3 [18]. It has been reported that PbI 2 has a sharp transition peak at 2.5 eV, while the CH 3 NH 3 PbI 3 peak is broad [42]. The deceasing broadening term C 2 indicates that a higher level of hydration water results in a higher content of PbI 2 in perovskite films.…”
Section: Resultssupporting
confidence: 78%
“…Absorption peaks at 2.5 eV are also observed in our measurement, which can be attributed to another direct transition in CH 3 NH 3 PbI 3 [18]. It has been reported that PbI 2 has a sharp transition peak at 2.5 eV, while the CH 3 NH 3 PbI 3 peak is broad [42]. The deceasing broadening term C 2 indicates that a higher level of hydration water results in a higher content of PbI 2 in perovskite films.…”
Section: Resultssupporting
confidence: 78%
“…PbI 2 is a direct transition semiconductor [77,78], although the α values near E g ~ 2.0 eV are very low [75,79]. A sharp optical transition at 2.5 eV in PbI 2 has been reported to be excitonic [78,80] and the transition energy of this peak is close to that of a CH 3 NH 3 PbI 3 peak observed in a similar energy region. However, the PbI 2 absorption peak at 2.5 eV is quite sharp, while the CH 3 NH 3 PbI 3 peak is very broad, suggesting that the origins of these transitions are different.…”
Section: Dft Calculationmentioning
confidence: 96%
“…Figure a shows the 2H‐polytype PbI 2 structure, in which the Pb atoms are surrounded by six I atoms and then forms an octahedral [PbI 6 ] 4− unit. The [PbI 6 ] 4− layers is bounded by weak vdW interactions with separation of 0.698 nm . In general, the unit cell of PbI 2 contains one Pb atom and two I atoms, where Pb atom occupies the top corner and I atoms locate at quarter positions in the lattice (Figure S1, Supporting Information).…”
mentioning
confidence: 99%